Enhancing Pharmacokinetics and Pharmacodynamics of Rosuvastatin Calcium through the Development and Optimization of Fast-Dissolving Films - Ibrahim Ashraf; Pierre A. Hanna; Shadeed Gad; Fathy I. Abd-Allah; Khalid M. El-Say (MDPI AG, 2023)
Rosuvastatin (RSV) is a widely used cholesterol-lowering medication, but its limited bioavailability due to its susceptibility to stomach pH and extensive first-pass metabolism poses a significant challenge. A fast-dissolving film (FDF) formulation of RSV was developed, characterized, and compared to the conventional marketed tablet to address this issue. The formulation process involved optimizing the thickness, disintegration time, and folding durability. All formulations were assessed for in vitro disintegration, thickness, folding endurance, in vitro dissolution, weight, and content uniformity. The study's results revealed that the optimized RSV-FDF displayed a significantly faster time to maximum plasma concentration (tmax) of 2 h, compared to 4 h for the marketed tablet. The maximum plasma concentration (Cmax) for the RSV-FDF (1.540 µg/mL ± 0.044) was notably higher than that of the marketed tablet (0.940 µg/mL ± 0.017). Additionally, the pharmacodynamic assessment in male Wistar rats demonstrated that the optimized RSV-FDF exhibited an improved lipid profile, including reduced levels of low-density lipoproteins (LDLs), elevated high-density lipoproteins (HDLs), decreased triglycerides (TGs), and lower very-low-density lipoproteins (VLDLs) compared to the conventional tablet. These findings underscore the potential of RSV-FDFs as a promising alternative to enhance the bioavailability and therapeutic efficacy of rosuvastatin in treating dyslipidemia. The faster onset of action and improved lipid-lowering effects make RSV-FDFs an attractive option for patients requiring efficient cholesterol management.